Application of the Sufficiency Economy Philosophy of Reducing Household Expenses of Farmers in Ban Thung-Sri, Phrae Province - Thongluea, Thira; Maifaey, Viganda (Area Based Development Research Journal, 2019)
This Participatory Action Research (PAR) aims to study the application of the sufficiency economy philosophy in reducing household expenses of farmers in the context of Thung-Sri area, Phrae province. Data are collected from 40 farmers in 51 families who participate in reducing household expenses activities for a year (January 2014 - May 2015). There are 4 activities: planting vegetables around the house, earthworm farming for castings and waste disposal, making products for household use, and making biological organic fertilizer. The research shows that by planting vegetables and raising earthworms to make organic fertilizers and household products, the farmers can cut down their household expenditure, especially on chemical fertilizers, vegetables, and household expense.